Zinc transporter ZIP10 supports zinc homeostasis and myoglobin biosynthesis in differentiating C2C12 myoblasts - Shim, Geonu; Kim, Min Ji; Ryu, Moon-Suhn (Frontiers in Cell and Developmental Biology, 2025)
BackgroundZinc is an essential micronutrient required for diverse cellular processes, including skeletal muscle development and regeneration. Although skeletal muscle contains a large proportion of total body zinc, the mechanisms that maintain zinc homeostasis during myoblast differentiation, particularly under zinc-limited conditions, remain poorly understood.MethodsWe investigated ZIP10 (SLC39A10) as the primary zinc importer responsible for maintaining intracellular zinc homeostasis under fluctuating zinc conditions during C2C12 myoblast differentiation. Zinc levels were modulated using zinc chelation or supplementation, and ZIP10 expression was repressed by gene silencing. Molecular and functional signatures of myogenesis were assessed through gene and protein expression analyses and nitric oxide (NO) metabolite profiling.ResultZinc deficiency markedly reduced the expression of the muscle-specific transcription factor Myog, as well as Mb. Among the 14 Zip and 10 ZnT genes profiled, Zip10 showed the largest fold increase in response to zinc depletion. Zip10 knockdown had minimal effects under zinc-sufficient conditions but further decreased Mb expression in zinc-deficient myoblasts without altering viability or major myogenic transcription factors. Notably, while zinc deficiency suppressed Mb expression, total cellular heme content remained unchanged, suggesting a zinc-dependent regulation of Mb biosynthesis independent of heme availability. Zinc deficiency also altered NO metabolism, as reflected by elevated nitrite levels and a reduced nitrate-to-nitrite ratio, indicating impaired Mb-mediated NO detoxification. Zinc addition elevated Mb expression and improved cell viability, with effects observed across both early and late differentiation phases.ConclusionThese findings identify ZIP10 as an important zinc importer that supports intracellular zinc supply and Mb expression during myogenic differentiation, offering new insight into the nutritional regulation of muscle physiology by zinc.